Credit Risk Management and Customer Satisfaction in Tier-one Deposits Money Banks: Evidence from Nigeria - Danjuma, Ibrahim; Kola, Ibrahim Abdullateef; Magaji, Badiya Yusuf; Kumshe, Hauwa Modu (International Journal of Economics and Financial Issues, 2016)
This study investigates the effect of credit risk management on customer satisfaction in tier-one deposits money banks in Adamawa state, Nigeria. The objectives of the study were to examine relationship between credit risk management and customers' satisfaction and to assess the relationship between credit risk management and credit appraisal process. The study surveyed 384 selected customers from three tier-one deposits money banks in Adamawa state, Nigeria. Purposive sampling was used in selecting the banks and simple random sampling was used in administering the questionnaire to the customers. Descriptive and inferential statistics were used to analyze and interpret the data collected. The study found that there is positive and significant relationship between credit risk management and customer satisfaction and the regression results showed that 49% of the variability in customer satisfaction can be explained by credit risk management. The study also found significant positive correlation between credit appraisal process and credit risk management, with 81% of the variability in credit appraisal process explained by credit risk management. The study recommends that despite the positive relationship between credit risk management and customer satisfaction, there is need for banks' management to pay attention to other factors that will contribute to customer satisfaction other than granting of credit facilities. At intervals, Banks should conduct seminars or training to update their staff on current credit guidelines issued by the regulatory authorities to enhance their knowledge on credit risk management with a view of ensuring customer satisfaction. Keywords: Credit Risk Management; Customer Satisfaction; Deposits Money Banks; Tier-one; JEL Classifications: M400, M30